Engendering Zionism : The Case of Emma Lazarus - Rottenberg, Catherine (Hagar: Studies in Society and Culture, 2003)
While many scholars have commented on the polemical aspects of Emma Lazarus ’ “Jewish ”poetry, most have concentrated on her use of religious and racial imagery but have failed to acknowledge the centrality of gender tropes in her writing. In this paper 1 examine Emma Lazarus’ attempt to reinvigorate Jewish patriotism and nationalism in 1880s America, contending that the nationalism Lazarus champions is informed by her efforts to create a “remasculinized" Jew. I argue that her endeavors were, in many ways, a reaction to the feminization of the Eastern European Jewish immigrants underway at the time. Emma Lazarus, a woman who precedes Zionism’s “founding fathers” - e.g., Herzl and Nordau - refigures Jewish maleness in hyper-masculine terms, and yet, in so doing, she unwittingly exposes the problematic nature of nationalism’s identity claims.